A rare case of scrotal emergency: torsion of epididymal cyst—a case report and literature review - Wang, Yu; Wang, Kai; Yu, Longdi; Ma, Xue (Frontiers in Pediatrics, 2024)
As a benign disease, the incidence of epididymal cyst (EC) is 5-25%, and it is relatively common in adults but rare in children. Although the pathogenesis of EC is still unclear, the symptoms of most asymptomatic patients can disappear with conservative treatment. EC torsion is even rarer in adults and children. Only ten cases have been reported in the literature, and we add this 3-year-old boy as the eleventh case of EC torsion. He was admitted to the hospital due to scrotum emergency without a history of EC or recent scrotal trauma. The ultrasonic examination revealed signs of an epididymal cyst. However, the pain and swelling of his scrotum were very similar to those of patients with testicular torsion, so we performed surgery on him. Therefore, EC torsion is very necessary to attract our attention as a differential diagnosis of testicular torsion in scrotal emergencies. Furthermore, our case is also the second youngest case of EC torsion.